Analysis of Intrinsic Elements of The Novel a Portion of Chicken Mie Before Diing By Brian Khrisna - Anggi, Nopita; Rosalina, Sinta; Triyadi, Slamet (Jurnal Indonesia Sosial Sains, 2025)
This study aims to describe the intrinsic elements contained in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna. The type of research in this study is descriptive qualitative. The data of this study are in the form of quotations of sentences containing intrinsic elements in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna. The data source of this study is the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna. The data was obtained by researchers using the reading, listening, and note-taking techniques. The data analysis technique uses descriptive analysis studies. The results of this study reveal that the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna has the theme of mental health and the meaning of a simple life. There are 12 active characters in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna with various characters or characterizations. The plot used in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna is a forward plot. The setting in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna is divided into 3 parts, namely the setting of place, setting of time, and setting of atmosphere. The novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna uses the first person point of view (I). Metaphor, paradox, and simile are figurative language found in Brian Khrisna's novel Seporsi Mie Ayam Sebelum Mati (A Portion of Chicken Noodles Before Dying). Overall, Seporsi Mie Ayam Sebelum Mati conveys that life can be saved through simple things, as long as one is given the space to be accepted and cared for.